On the Imperative of Language for Understanding African Art - Rowland Abiodun (Yoruba Studies Review)
I was deeply touched and honored by the roundtable organized at the 2016 African Studies Association Conference to focus on my book, Yoruba Art and Language: Seeking the African in African Art (2014). I want to thank Professor Funṣọ Afọlayan for contacting and bringing together a formidable group of scholars of Yorùbá art and culture to that end. I was gratified that, by and large, all the panelists endorsed my premise on the fundamental importance of language in Yorùbá art studies. The first paper by Moyọ Okediji was a pleasant surprise. Even though this possibility has always existed, as I had taught a course in Yorùbá art entirely in Yorùbá language at the University of Ifẹ (renamed Ọba ̀ ́fẹmi Awo ́ ́lọẃ ọ University) in ̀ the 1980s1 , no one was expecting that his entire contribution to the roundtable discussion would be presented in Yorùbá language. Why not? I realized. The language is as fully developed as any other language in the world and it can, and should be spoken as well as written -- especially when we discuss Yorùbá art. For the benefit of those not literate in Yorùba language, Michael Af ́ ọlayan gave an elegant translation of Okediji’s paper in English. The excellent contents and presentation by Okediji touched on issues that lay at the heart of my book, namely its methodology and its insistence on the need for a Yorùbá voice to be heard literally and metaphorically in art historical discourse.